User Satisfaction Analysis of Access Kai Application Using Delone and Mclean Method Approach - Oktaviani, Juwita; Retnowardhani , Astari (Jurnal Indonesia Sosial Sains, 2025)
Access KAI application is a mobile application like e-commerce that sell various kinds of service related to train travel in Indonesia officially developed by PT. Indonesian Railways. PT. KAI has collaborated with other e-commercial application as a partner like Traveloka and Tiket.com to sell their intercity train tickets. The main purpose of this study is to analyze factors that influence user satisfaction and give the insight for the company. This research was conducted using the Delone and Mclean model that aims to identify and evaluate factors the influence of Information Quality, System Quality, Service Quality, and Intention to Use, against the User Satisfaction. This study involves analyzing data with the SEM-PLS analysis tools (Structural Equation Modelling) using SmartPLS 4 by testing data that has been collected through online questionnaire from Google Forms to 400 respondents. The study was conducted with 26 questions derived from 5 variables. These 5 variables are analyzed the validity and reliability levels. Then if all are said to be valid and reliable, the model will be tested using the PLS and Bootstrapping methods. The results of the validity and reliability test were declared valid and reliable. The result of test of proposed research model showed that system quality and intention to use have a positive and significant correlation (p-value<0.01) on user satisfaction. While information quality and service quality have no significant correlation (p-value>0.01) on user satisfaction. Thus, the result of this study states that only system quality and intention to use is stated to have a significant effect in influencing user satisfaction.